The aqueducts of the sultanate of Oman: Sustainable water-supplying systems irrigating oases cities - Ragala, Rachid (2016)
This book presents the major engineering achievements in underground aqueducts from around the world and throughout history. It provides valuable insights into water technologies and management with respect to durability, adaptability to the environment, and sustainability. Comparisons of the technological underground aqueduct developments from several regions are made. These technologies are the underpinning of modern achievements in water supply engineering and water management practices, and current issues of sustainability, cost-effectiveness, and decentralization have led engineers to consider combining older proven technologies with modern infrastructure advancements